Highly dispersed MnOx–FeOx supported by silicalite-1 for the selective catalytic reduction of NOx with NH3 at low temperatures. Issue 16 (17th July 2020) - Gu, Jialiang; Zhu, Bingjun; Duan, Rudi; Chen, Yan; Wang, Shaoxin; Liu, Lili; Wang, Xidong
Abstract : MnO x –FeO x -Loaded silicalite-1 catalysts exhibit high NO x conversion at low temperatures. Abstract : A silicalite-1-based catalyst with highly dispersed manganese and iron oxides was synthesized by the wet impregnation method for the selective catalytic reduction (SCR) of NO x with NH3 at low temperatures. The optimized catalyst demonstrated over 90% NO x conversion efficiency between 135 and 270 °C with a space velocity of 35 000 h −1, which can be attributed to the well-developed porous structure of silicalite-1 and the synergistic effects between silicalite-1 and supported metal oxide active sites. In addition, the porous structure and the addition of FeO x greatly promoted the dispersion of MnO x nanoparticles, which further improves the efficiency of SCR. Moreover, the reaction route for the NH3 -SCR reaction was further investigated by in situ diffuse reflectance infrared Fourier transform spectroscopy ( in situ DRIFTS). The corresponding test results indicate that the reaction route follows both Eley–Rideal (E–R) and Langmuir–Hinshelwood (L–H) mechanisms.